THE USE OF SPENT BLEACHING EARTH (SBE) AS AN ADSORBENT TO REDUCE FREE FATTY ACIDS IN WASTE COOKING OIL - Dianindita Rizki Maharani; Ratnaningsih Ruhiyat; Bambang Iswanto; Any Juliani (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
High free fatty acids in waste cooking oil can interfere with the re-use of the cooking oil. Therefore, the absorption technique is one way that can reduce the free fatty acids contained in waste cooking oil. Aim: The purpose of this study is to find out the ability of Reactivated Spent Bleaching Earth (RSBE) to adsorb free fatty acids contained in waste cooking oil to be biodiesel products. In this study, waste cooking oil was collected from fried food sellers in Bekasi, while spent bleaching earth (SBE)-one of the solid wastes produced by refinery oil palm industry as an adsorbent-was from the palm oil industry PT X. For Reactivated Spent Bleaching Earth (RSBE), the redundant used 0.7 M HNO3. To obtain the optimum products, The redundant applied the variation of time (i.e., 30, 45, 60, 75, and 90 minutes) and concentration (6%, 9%, 12%, 15%, and 18%). Methodology and results: Results indicated that the time variation of temperature 90 minutes were the maximum and the concentration of 15% were the optimal combination to reduce free fatty acids 0.65%. Conclusion, significance, and impact of study: The values of water and ash contents of RSBE also meet the quality standard as activated carbon and can be used as an adsorbent for the purification of waste cooking oil. The oil content in SBE is less than 3% and is considered not to be a toxic hazardous waste. Therefore, it can be reused without pre-treatment. In addition, the redundant found that there were changes pore on the surface of the SBE, both activated and not activated. To conclude, SBE can be used as an absorbent to absorb the fatty acids in waste cooking oil.